Performance and Quantitative Characteristics of Linus Native Chicken Given Moringa Leaf Flour with Different Processing Methods and Levels of Administration - Muhammad Nur Hidayat (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2022)
This study aims to determine the processing method and level of giving flour moringa leaves which are good for performance and quantitative characteristics of linus native chickens. This study used linus chickens aged 15 days as many as 54 tails. This study used Ccmpletely randomized designompletely Randomized Design (CRD) with a 3×3×3 factorial pattern where 3 treatments were factor I (processing method) and 3 treatments were factor II (administration level) using 3 replications. Factor I consists of M1 steam processing method, M2 fermentation processing method, M3 withering processing method, in factor II consists of P1 level of administration ofthoe 2%, P2 level of administration ofthoe 4%, P3 level of administration ofthoe 6%. The parameters observed in this study were ration consumption, body weight gain, ration conversion, drinking water consumption, shank length (legs), wing length and body length. The results showed that each treatment had no significant effect (P0,05) on the performance and quantitative characteristics.